Effectiveness of Indigenous Rhizobacteria Formulations in Increasing the Growth and Yield of Shallots (Allium ascalonicum L.) - Sutariati, Gusti Ayu Kade; Madiki, Abdul; Hariani, Ni Kadek Dwi; Mudi, La; Khaeruni, Andi; Wibawa, Gusti Ngurah Adi; Afa, Musadia (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2021)
The use of beneficial microbes in increasing plant growth and yield is a very appropriate choice to reduce synthetic chemicals that can cause negative impacts on the environment. The purpose of this study was to evaluate the effectiveness of post-save formulations of Wakatobi indigenous rhizobacteria in increasing the growth and yield of shallots. The study was conducted in Jati Bali Village, Konawe Selatan District, using a Randomized Block Design, consisting of 10 rhizobacterial formulation treatments, a combination of three types of biological agents, namely Pseudomonas sp. LP03, Pseudomonas sp. TWB02 and Pseudomonas sp. TWB11, and three types of formulation materials: ground brick powder, ground burned rice husk powder, and bentonite; one control using NaCl 0.85%. The experiment was repeated three times so that there were 360 treatment units. The results showed that of the three types of rhizobacteria tested, only Pseudomonas sp. TWB02 and Pseudomonas sp. LP03 can display better performance in increasing the growth and yield of shallots. These rhizobacteria are more compatible using the ground burned rice-husk powder formulation. Increased shallot yield (tuber fresh weight) in seed treatment using Pseudomonas sp. TWB02 and Pseudomonas sp. LP03 in the formulation of ground burned rice-husk powder reached 121% and 117% compared to controls. Further research needs to be done on a broader scale and different environmental conditions to see the stability of these biological agents' effects on the growth and yield of shallots.